Structural signature and size-dependent mechanical response of frozen-in icosahedral phase in bulk metallic glasses. (15th January 2018) - Chang, Hye Jung; Oh, Hyun Seok; Lee, Je In; Park, Eun Soo
Abstract: In the present study, we report structural signature and size-dependent mechanical response of frozen-in icosahedral phase (I-phase) embedded in Zr-(Ti, Nb, Al)-(Cu, Ni) bulk metallic glass (BMG)-forming alloys, which exhibit a narrow composition range overlapping between glass and I-phase forming region. Thus, the different sizes of the I-phase from tens of nanoscale precipitates to enhanced icosahedral short-range order in MG matrix can be obtained by controlling cooling history. I-phase particles with tens of nanoscale in BMGs do not contribute to extrinsic ductility due to limited blocking of the propagation of shear band. The shear band passes through the particle, splitting it into two pieces. On the other hand, BMGs with enhanced icosahedral short-range order, which can be evaluated by EXAFS analysis as well as calorimetric signal during isothermal annealing, exhibit enhanced ductility without strength reduction. Indeed, we examine the cut-off size of strain bursts and deformation dynamics of shear-avalanches through the statistical analysis of serration behavior. Icosahedral short-range order (ISRO)-embedded MGs exhibit weakened jammed state of the self-organized deformed zones, which results in the formation of numerous catastrophic deformed zones under relatively chaotic dynamics, and consequently multiple shear bands. These results would help deepen our understanding of the underlying mechanism that determines intrinsic ductility in BMGs via frozen-in ISRO, and ultimately give us a guideline for the design of promising BMGs with improved intrinsic ductility by manipulating local structural instability. Graphical abstract: Highlights: Our study highlights the importance of the manipulation of Icosahedral SRO in BMG-forming alloys to enhance ductility. Frozen-in icosahedral 2 nd phase with tens of nanoscale in BMG does not block the propagation of shear band. Frozen-in ISRO results in enhanced plasticity up to 4.64% with uniquely large slip avalanches without strength reduction. BMG with ISRO exhibits smaller Sc and β, which cause easy plastic dynamic transition from jamming to unjamming states. Our results provide a direct connection of atomic-scale instability and shear-avalanche dynamics during deformation in BMG.